Exploring dual-lidar mean and turbulence measurements over Perdigão's complex terrain - I. L. Coimbra; J. Mann; J. M. L. M. Palma; V. T. P. Batista (Atmospheric Measurement Techniques)
To assess the accuracy of lidars in measuring mean wind speed and turbulence at large distances above the ground as an alternative to tall and expensive meteorological towers, we evaluated three dual-lidar measurements in virtual-mast (VM) mode over the complex terrain of the Perdigão-2017 campaign. The VMs were obtained by overlapping two coordinated range height indicator scans, prioritising continuous vertical measurements at multiple heights at the expense of high temporal and spatial synchronisation. Forty-six days of results from three VMs (VM1 on the SW ridge, VM2 in the valley, and VM3 on the NE ridge) were compared against sonic readings (at 80 and 100 m a.g.l.) in terms of 10 min means and variances to assess accuracy and the influence of atmospheric stability, vertical velocity, and sampling rate on VM measurements. For mean flow quantities – wind speed (Vh) and u and v velocity components – the r2 values were close to 1 at all VMs, with the lowest equal to 0.948, whereas in the case of turbulence measurements (u′u′<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="22pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="175047d0c6687ee2e4ebddc0fafc2677"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-287-2025-ie00001.svg" width="22pt" height="11pt" src="amt-18-287-2025-ie00001.png"/></svg:svg> and v′v′<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="21pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="716e4068f348c1250f139d0cb4b1cea3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-287-2025-ie00002.svg" width="21pt" height="11pt" src="amt-18-287-2025-ie00002.png"/></svg:svg>), the lowest was 0.809. Concerning differences between ridge and valley measurements, the average RMSE for the wind variances was 0.295 m2 s−2 at the VMs on the ridges. In the valley, under a more complex and turbulent flow, smaller between-beam angle, and lower lidars' synchronisation, VM2 presented the highest variance RMSE, 0.600 m2 s−2 for u′u′<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="22pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="2f47087a259cfa593d793f1274636f43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-287-2025-ie00003.svg" width="22pt" height="11pt" src="amt-18-287-2025-ie00003.png"/></svg:svg>. The impact of atmospheric stability on VM measurements also varied by location, especially for the turbulence variables. VM1 and VM3 exhibited better statistical metrics of the mean and turbulent wind under stable conditions, whereas at VM2, the better results with a stable atmosphere were restricted to the wind variances. We suspect that with a stable and less turbulent atmosphere, the scan synchronisation in the dual-lidar systems had a lower impact on the measurement accuracy. The impact of the zero vertical velocity assumption on dual-lidar retrievals at 80 and 100 m a.g.l. in Perdigão was minimal, confirming the validity of the VM results at these heights. Lastly, the VMs' low sampling rate contributed to 33 % of the overall RMSE for mean quantities and 78 % for variances at 100 m a.g.l., under the assumption of a linear influence of the sampling rate on the dual-lidar error. Overall, the VM results showed the ability of this measurement methodology to capture mean and turbulent wind characteristics under different flow conditions and over mountainous terrain. Upon appraisal of the VM accuracy based on sonic anemometer measurements at 80 and 100 m a.g.l., we obtained vertical profiles of the wind up to 430 m a.g.l. To ensure dual-lidar measurement reliability, we recommend a 90° angle between beams and a sampling rate of at least 0.05 Hz for mean and 0.2 Hz for turbulent flow variables.